Addressing the perpetuation of violence and impunity: a call for reforming the definition and enforcement of genocide - Turrecha, Steven (My University, 2025)
The heinous crime of genocide is an abomination that strikes at the very core of humanity. It represents the ultimate harm that can be inflicted upon a group of people, as it involves not only the extinguishment of their lives but also the eradication of their cultural existence. To provide a broader conceptual definition of genocide, Presser (2013) states, “Genocide has been called ‘the crime of crimes’ (Schabas, 2000). It strikes us as the worst possible harm because its eliminationist intent is absolute and explicit, because large numbers of people are harmed or meant to be harmed, and because it is often associated with unthinkable atrocities” (p.31). Despite the grave nature of this crime and the numerous atrocities and harms that are associated, this paper will argue that the current legal definition of genocide, as it is currently applied, contributes to the perpetuation of violence and aggression by being too narrow and selectively enforced, allowing those in positions of power to act with impunity. Thus, there is a pressing need to restructure international procedures overseeing global conflicts and amend the current application of international law to address these concerns. A point of focus of this paper will be the mass atrocities committed against the Tutsi minority during the Rwandan Genocide in 1994, in conjunction with the failed peacekeeping efforts by the United Nations and their role in the catastrophe in order to demonstrate the fallibility of international law and the shortcomings of mainstream criminology within the context of genocide.
Keywords: genocide; reform; critical criminology; United Nations